2015
DOI: 10.1002/14651858.cd003366.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Taxane-containing regimens for metastatic breast cancer

Abstract: BackgroundIt is generally accepted that taxanes are among the most active chemotherapy agents in the management of metastatic breast cancer. This is an update of a Cochrane review first published in 2003. ObjectivesThe objective of this review was to compare taxane-containing chemotherapy regimens with regimens not containing a taxane in the management of women with metastatic breast cancer. Search methodsIn this review update, we searched the Cochrane Breast Cancer Group Specialised Register, MEDLINE, EMBASE,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(24 citation statements)
references
References 63 publications
0
21
0
3
Order By: Relevance
“…Currently, taxanes are considered the most effective cytotoxic drugs for the treatment of MBC, both in monotherapy and combination schedules, with a proven survival benefit compared with the use of other types of chemotherapy. Paclitaxel and docetaxel, the two most commonly used taxanes against breast cancer, are the agents of choice in patients progressing after anthracycline-containing chemotherapy according to the most recent international guidelines [Ghersi et al 2003;Cardoso et al 2014]. These two agents were both registered as 3-weekly (q3w) regimens, but different doses and schedules were subsequently tested aiming at increasing efficacy and at reducing the burden of treatment-related toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, taxanes are considered the most effective cytotoxic drugs for the treatment of MBC, both in monotherapy and combination schedules, with a proven survival benefit compared with the use of other types of chemotherapy. Paclitaxel and docetaxel, the two most commonly used taxanes against breast cancer, are the agents of choice in patients progressing after anthracycline-containing chemotherapy according to the most recent international guidelines [Ghersi et al 2003;Cardoso et al 2014]. These two agents were both registered as 3-weekly (q3w) regimens, but different doses and schedules were subsequently tested aiming at increasing efficacy and at reducing the burden of treatment-related toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…A 2005 meta-analysis from the Cochrane Collaboration noted that when all trials are considered, taxane-containing regimens appear to improve os, ttp, and overall response in women with metastatic breast cancer 63 . Another meta-analysis found that, although there are potential differences in rr and pfs, taxanes are equivalent to anthracyclines (either as single agents or in combination) in terms of os benefit 64 .…”
Section: Taxanesmentioning
confidence: 99%
“…It has been used to treat various tumors, particularly tumors of the breast (Bear et al, 2003;Jones et al, 2006), lung (Noble et al, 2006) and prostate (Kelly et al, 2009). Its use can bring benefits such as increasing life expectancy and decreasing tumors, tumor progression and risk of relapse (Ghersi et al, 2015). It is used as a first-line therapeutic treatment in combination with trastuzumab, a monoclonal antibody specific for HER2 receptor in metastatic breast cancers that express the HER2 receptor.…”
Section: Introductionmentioning
confidence: 99%